Agnes and Nicole's Sexual Discrimination in Margaret Atwood’s The Testaments - Mufarida, Lilis (Journal of Literature, Linguistics, & Cultural Studies, 2022)
The phenomenon of sexism still existed in society. Sexism came from the negative stereotypes that assumes one gender is more valuable than the other. In this research, sexism was manifested in the literary work. One of them Margaret Atwood's The Testaments. This research aimed to describe the form of sexism experienced and it was effected by the main characters in Margaret Atwood's The Testaments. It will be focused on Agnes and Nicole. Then, it used feminist literary criticism method with feminism approach. This research sought to solve the research problems based on applying library research techniques by reading repeatedly and then taking a note. Then, the data were analyzed using the ambivalent sexism theory proposed by Glick and Fiske. The data analysis technique used content analysis. Content analysis was an in-depth analysis of the messages contained in a text. Furthermore, the finding data revealed that sexism experienced by the main characters, including: not being allowed to read and write, obligation to cover their body, arranged marriage, women constructed in domestic roles, and living in limited freedom. Then, the effect of sexism was revealed, including sexual harassment, objectification, internalized sexism, and alienation. Furthermore, the main characters' resistance is liberation and taking a mission.